Al/Mn co-doping endows V2O54VO2 cathode with enhanced lithium storage performance. (1st January 2022) - Zhang, Shuchao; Zou, Zhengguang; Zhong, Shenglin; Meng, Jianying; Liu, Xin; Xu, Shuxin; Li, You; Peng, Xiaoxiao; Ling, Wenqin
Abstract: The vanadium oxide V2 O5 4VO2 cathode material has aroused significant interest due to its high theoretical capacity and wide availability. However, the poor rate and cycle performance of the V2 O5 4VO2 electrode severely hindered its further application in high-energy density lithium-ion batteries. Herein, a kind of Al/Mn co-doped V2 O5 4VO2 prepared via facile solvothermal method combined with annealing process was reported. Theoretical and experimental results reveal that [AlO6 ] and [MnO6 ] not only serve as an octahedral pillar to extend the interlayer spacing, but introduce oxygen vacancies that provide more lithium ion active sites and higher ionic and electronic conductivity in lithium ion (de)intercalation process. Paired with lithium metal anode, Al/Mn co-doped V2 O5 4VO2 cathode exhibits better performance metrics of 322.5 mAh/g at 0.1 A/g, 91.7% capacity retention after 50 cycles, and 195.8 mAh/g after 200 cycles at a current density of 1 A/g, while the values corresponding to the pure phase V2 O5 4VO2 are 248.7 mAh/g, 66.9% as well as 97.7 mAh/g respectively. Actually, the insight into the performance of potential electrode materials improved by double ion doping was provided in the present work.